PEMETAAN JALUR INTERPRETASI EKOWISATA DI DESA PAHMUNGAN, KABUPATEN PESISIR BARAT - Rio Rahmad Akmal; Gunardi Djoko W; Trio Santoso (Jurnal Hutan Tropis, 2021)
Ecotourism usually has an educational value packed in the form of natural beauty and is in the countryside. Lampung has many potential ecotourism, one of which is located in West Coast district. This research was conducted in March 2019 to April 2019 in Pahmungan Village, central Coastal district, West Coast Regency, Lampung province.  The Pekon or the village of Pahmungan has an area of 2,600 ha, Pekon Pahmungan is located at 5 ° S and 103 ° E and is 4 km from the centre of the district government, 32 km from the county capital, and 287 km to the provincial capital. Data collection methods used are methods of surveys, interviews, and GIS while the method of data analysis used is a qualitative descriptive method. The purpose of this research is the development of tourism potentials and make the route of ecotourism Intermap in Pahmungan village. The tools used in this study are GPS (Global Positioning System), Camera, Compass, Laptop, and ArcGis application. The object in this research is the ecotourism object that exists in Pahmungan village that will be obtained through the observation of field surveys and interviews with local communities. The results of this research are reflected in the mapping of tourist interpretation lines in which the mapping is an ecotourism pathway that includes various tours in the village Pahmungan. Ecotourism in the village of Pahmungan is not well managed but there are already several community who began to build the development of tourist destinations especially the waterfall tourism, with the program interpretation programs can support the development of Ecotourism and provide comfort for visitors.